Finite Element Model for Prediction of Highway Pavement Deformation (Global Journals of Research in Engineering, 2023)
The determination of stresses developed in a pavement constitutes a basic prerequisite and is achieved mainly by implementation of various methods which is dependent on the number of distinct pavement layers The need to predict the deformation of highway pavement with a precision that will aid optimal design cannot be oversized Boussinesq s work was foundational for the development of all subsequent elasticity theories but Boussinesq assumed one layer of uniform subgrade material In this research a mechanistic elastic model for obtaining deformation in road pavement was derived using Finite Element Method FEM This model was found to be an improvement on the Boussinesq model owing to the closeness of its result to that obtained from Plaxis software In addition to this it has the capability of handling deformation in both flexible and rigid pavement utilizing the dimensional similarities between unit weight and modulus of subgrade reaction of soil A MATLAB program was also written for easy computation using the new model
Keywords: pavement deformation; finite element model; boussinesq’s model; MATLAB program